Identify and Analyse Challenges Associated with Green Procurement Practices in the Cement Industry - Sharda, Nikhil; Mathur, Dipin (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The research work explores the difficulties encountered in the adoption of environmentally sustainable procurement methods within the cement production sector. An examination of critical elements including elevated expenses, regulatory challenges, restricted access to sustainable resources, supplier opposition, and insufficient awareness reveals notable obstacles to implementation. The results suggest that these obstacles affect the sector’s capacity to adopt sustainable procurement practices. The findings validate the impact of awareness, the accessibility of sustainable resources, and the presence of support systems on the adoption of green procurement practices. The analysis highlights the necessity for policy reforms, financial incentives, supplier engagement, and educational initiatives to address these obstacles. Tackling these challenges will improve sustainability, ensure regulatory compliance, and bolster corporate social responsibility within the cement industry.